Title: The effects of corrective exercises on kyphosis and balance among educable mentally retarded adolescents. - Mohammad Sadegh Sarkhosh; Mehrdad Anbarin; Mostafa Sepehrian; Mohamad Ali Samavatsharif; Alireza Rahimi (Vesnu Publications, 2015)
Introduction: Individuals with mental retardation due to a wrong attitude that exists among the people usually are inactive. Inactivity and taking the wrong position can cause thoracic kyphosis abnormality consequently, reducing the balance. The purpose of this study was to determine the effects of a 6-week corrective exercise training program on amount of thoracic kyphosis and balance in individuals with mental disability. Materials and methods: In this quasi-experimental study, 30 mentally retarded adolescents with increased thoracic kyphosis were randomly assigned into experimental or control groups (15 in each group). The control group was asked to continue their routine life as usual, while subjects in experimental group underwent a 6-week corrective exercise program. Before and after the exercise program, the amount of thoracic kyphosis, dynamic and static balance were measured by flexible ruler, the heel to toe walking test and foot scan system for 25 seconds, respectively. Data were analyzed using independent t-test (p≥0.05). Results: Our results showed that corrective exercise program decreased the amount of thoracic kyphosis (p=0.001) and improved the static (p=0.001) and dynamic balance (p=0.001) in experimental group. There were no significant changes in the control group. Conclusions: According to the results, corrective exercises can be reduced the degree of thoracic kyphosis and improve both dynamic and static balance abilities in mentally retarded individuals. These results suggest the need of physical activity and exercises for mentally retarded adolescents. Keywords: Educable mentally retarded, Kyphosis, Static balance, Dynamic balance